Microwave-assisted direct coupling of graphene nanoplatelets with poly ethylene glycol and 4-phenylazophenol molecules for preparing stable-colloidal system - Amiri, A.; Shanbedi, M.; Ahmadi, G.; Eshghi, H.; Chew, B.T.; Kazi, S.N. (Elsevier, 2015)
Herein, microwave-assisted direct coupling of Graphene Nanoplatelets (GNP) with polymers including hydroxyl ( OH) groups such as poly ethylene glycol (PEG) and bio-molecules like 4-phenylazophenol (Azo) are investigated. Among different water-soluble polymers, PEG has received unique consideration due to its biocompatibility. Moreover, Azo-treated GNP can easily employ in long-term solar thermal storage. Thus, an electrophilic addition reaction under microwave irradiation is presented as an efficient procedure to functionalize GNP with Azo and PEG. In order to compare the activities of different catalysts under microwave irradiation, the direct coupling of GNP with Azo and PEG were performed in the presence of ZnCl2, FeCl2,TiCl4 and AlCl3, separately. The use of simple Lewis acids loading provides an electrophilic addition reaction in as little as 30 min, which provide a shortcut and prevent time-consuming and multiple steps approaches. Interestingly, PEG-treated GNP has no cross-linking of the flakes, which this allows the production of more dispersed GNP in aqueous media. Investigation of colloidal stability using particle absorbance measurement showed successful results in terms of stability with very low sediment. (C) 2015 Elsevier B.V. All rights reserved.